Allosteric Transitions Direct Protein Tagging by PafA, the Prokaryotic Ubiquitin-like Protein (Pup) Ligase - Ofer, Naomi (American Society for Biochemistry and Molecular Biology, 2013)

(untitled)
Protein degradation via prokaryotic ubiquitin-like protein (Pup) tagging is conserved in bacteria belonging to the phyla Actinobacteria and Nitrospira. The physiological role of this novel proteolytic pathway is not yet clear, although in Mycobacterium tuberculosis, the world's most threatening bacterial pathogen, Pup tagging is important for virulence. PafA, the Pup ligase, couples ATP hydrolysis with Pup conjugation to lysine side chains of protein substrates. PafA is the sole Pup ligase in M. tuberculosis and apparently, in other bacteria. Thus, whereas PafA is a key player in the Pup tagging (i.e. pupylation) system, control of its activity and interactions with target protein substrates remain poorly understood. In this study, we examined the mechanism of protein pupylation by PafA in Mycobacterium smegmatis, a model mycobacterial organism. We report that PafA is an allosteric enzyme that binds its target substrates cooperatively and find that PafA allostery is controlled by the binding of target protein substrates, yet is unaffected by Pup binding. Analysis of PafA pupylation using engineered substrates differing in the number of pupylation sites points to PafA acting as a dimer. These findings suggest that protein pupylation can be regulated at the level of PafA allostery.